The Definitive Guide to Stellent Content Server Development - Huff, Brian (Apress : Imprint: Apress, 2006)
The Definitive Guide to Stellent Content Server Development is the most complete book available for this enterprise content management application. It gives an introduction to content management, followed by an in-depth discussion of Stellent's core service-oriented architecture. It details how its flexible, component-driven model makes it easy to customize the appearance and behavior of the server. Focusing on the developer, this book gives step-by-step examples for creating data entry forms, designing skins, adding services, customizing the web interface, integrating with other applications, and modifying the behavior with Java. Throughout the book the author reveals tips and tricks on security, performance, metadata design, maintenance, undocumented features, and general best practices. It is complete with appendices detailing the inner working of the Content Server. This includes a full discussion about the IdocScript language, the JSP integration layer, and some of the internal Java APIs. You will find this a vital resource whether you're just considering Stellent, or you own it and want to customize it to fit your exact needs.